Owly - Thaler, Mike, 1936-; Wiesner, David (New York, N.Y. : Harper & Row, 1982)
When Owly asks his mother question after question about the world, she finds just the right ways to help him find the answers.
Keywords: Owls -- Fiction; Parent and child -- Fiction